La villa di Piero Del Tovaglia a Santa Margherita a Montici presso Firenze - Guza, Kamela (Opus Incertum, 2019)
Piero del Tovaglia — procurator and factotum of Ludovico Gonzaga in Florence – participated actively in the tormented affaire of the building of the Tribune in Santissima Annunziata, showing a complete loyalty towards the solution proposed by Leon Battista Alberti. This successful task led him into the very core of the architectural debate in Florence and allowed him to get in touch with the most important architects and patrons of the time. In the last decades of the 15th century he decided to build a villa near the city, in Santa Margherita a Montici. The new building was inserted in a pre-existing organism and consists basically of a hall covered by a coffered barrel vault, with symbols related to the families of the Gonzaga and Este, and is representative of the updated architectural culture of its patron and of his social prestige. The monolithic compactness and the isolation from the medieval pre-existing structures emphasize the exceptional nature and modernity of the building, which seems to have caught the attention of Leonardo da Vinci at the beginning of the 16th century.